BnSIP1-1, a Trihelix Family Gene, Mediates Abiotic Stress Tolerance and ABA Signaling in Brassica napus - Luo, Junling; Tang, Shaohua; Mei, Fengling; Peng, Xiaojue; Li, Jun; Li, Xiaofei; Yan, Xiaohong; Zeng, Xinhua; Liu, Fang; Wu, Yuhua; Wu, Gang (Frontiers in Plant Science, 2017)
The trihelix family genes have important functions in light-relevant and other developmental processes, but their roles in response to adverse environment are largely unclear. In this study, we identified a new gene, BnSIP1-1, which fell in the SIP1 (6b INTERACTING PROTEIN1) clade of the trihelix family with two trihelix DNA binding domains and a fourth amphipathic α-helix. BnSIP1-1 protein specifically targeted to the nucleus, and its expression can be induced by abscisic acid (ABA) and different stresses. Overexpression of BnSIP1-1 improved seed germination under osmotic pressure, salt and ABA treatments. Moreover, BnSIP1-1 decreased the susceptibility of transgenic seedlings to osmotic pressure and ABA treatments, whereas there was no difference under salt stress between the transgenic and wild-type seedlings. ABA level in the transgenic seedlings leaves was higher than those in the control plants under normal condition. Under exogenous ABA treatment and mannitol stress, the accumulation of ABA in the transgenic plants was higher than that in the control plants; while under salt stress, the difference of ABA content before treatment was gradually smaller with the prolongation of salt treatment time, then after 24 h of treatment the ABA level was similar in transgenic and wild-type plants. The transcription levels of several general stress marker genes (BnRD29A, BnERD15, and BnLEA1) were higher in the transgenic plants than the wild-type plants, whereas salt-responsive genes (BnSOS1, BnNHX1, and BnHKT) were not significantly different or even reduced compared with the wild-type plants, which indicated that BnSIP1-1 specifically exerted different regulatory mechanisms on the osmotic- and salt-response pathways. Overall, these findings suggested that BnSIP1-1 played roles in ABA synthesis and signaling, salt and osmotic stress response. To date, information about the involvement of the B. napus trihelix gene in abiotic response is scarce. Here, we firstly reported abiotic stress response and possible function mechanisms of a new trihelix gene in B. napus.